Isolation and ultra-high performance liquid chromatography analysis of zerumbone and zerumbone epoxide in Zingiber zerumbet rhizomes - Kongkiatpaiboon, Sumet; Saereewat, Chutharat; Tayana, Ngampuk; Duangdee, Nongnaphat; Inthakusol, Wichayasith (Agriculture and Natural Resources, 2023)
Importance of the work: Zingiber zerumbet (L.) Roscoe ex Sm. is an indigenous plant in Southeast Asia used in numerous ethnomedicinal applications and is of interest for pharmaceutical development. Objectives: To isolate, optimize the extraction and develop a rapid quantitative analysis of zerumbone and zerumbone epoxide in Z. zerumbet rhizomes. Materials & Methods: Chromatographic isolation of major components in the Z. zerumbet rhizomes yielded zerumbone and zerumbone epoxide. Their structures were identified using spectroscopic and spectrometric techniques. An ultra-high performance liquid chromatography (UHPLC) method was developed and validated for the quantitative analysis of zerumbone and zerumbone epoxide in the Z. zerumbet rhizomes. Suitable solvents for extracting Z. zerumbet were optimized. Results: The developed UHPLC method demonstrated good sensitivity, linearity, precision and accuracy. Ethanol was considered as a suitable extracting solvent to obtain high yields of bioactive components from Z. zerumbet rhizomes. The contents of zerumbone and zerumbone epoxide in the Z. zerumbet rhizomes from various locations of Thailand were analyzed based on their UHPLC chromatograms that indicated the homogeneity of Z. zerumbet in Thailand. Main finding: A rapid UHPLC method was developed and validated for quantitative analysis of zerumbone and zerumbone epoxide in Z. zerumbet rhizomes. A suitable extracting solvent (methanol) was optimized. The contents were analyzed of the zerumbone and zerumbone epoxide in the Z. zerumbet rhizomes from various locations of Thailand.